Exponential Stability of a Linear Distributed Parameter Bioprocess with Input Delay in Boundary Control. (6th August 2013) - Zheng, Fu; Fu, LingLing; Teng, MingYan
Abstract : We consider a linear distributed parameter bioprocess with boundary control input possessing a time delay. Using a simple boundary feedback law, we show that the closed-loop system generates a uniformly bounded C 0 -semigroup of linear operators under a certain condition with respect to the feedback gain. After analyzing the spectrum configuration of closed-loop system and verifying the spectrum determined growth assumption, we show that the closed-loop system is exponentially stable. Thus, we demonstrate that the linear distributed parameter bioprocess preserves the exponential stability for arbitrary time delays.